Anode material for lithium secondary battery, and manufacturing method thereof

KR103019296B1Active Publication Date: 2026-09-15LEMON ENERGY INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
KR1020250137599
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-09-23
Publication Date
2026-09-15
Estimated Expiration
2045-09-23

Smart Images

  • Figure 112025108976079-PAT00006_ABST
    Figure 112025108976079-PAT00006_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode material for a lithium secondary battery and a method for manufacturing the same. In one embodiment, the negative electrode material for a lithium secondary battery comprises a porous carbon carrier; nanosilicon filled in the pores of the carbon carrier; a first coating layer formed on the outer surface of the carbon carrier; and a second coating layer formed on the outer surface of the first coating layer, having a lower hardness than the first coating layer; wherein the carbon carrier has a higher hardness than the second coating layer, and the negative electrode material has a D-band peak intensity (ID / IG) relative to the G-band peak intensity in a Raman spectrum of 1.3 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a negative electrode material for a lithium secondary battery and a method for manufacturing the same. Background Technology

[0003] As the applications of lithium-ion batteries become more diverse, there is a demand for batteries with high energy density; accordingly, research and development aimed at increasing the capacity of cathode and anode active materials have been carried out in parallel.

[0004] Currently, commercially available negative electrode active materials are graphite. During the charging process, where lithium ions move from the positive electrode to the negative electrode, the lithium ions that reach the negative electrode are stored between the graphite layers. At this time, the graphite incorporating lithium ions expands, causing a slight increase in volume. If this process is repeated, it gradually leads to structural changes, which in turn reduces battery life. Therefore, the negative electrode material is one of the critical factors determining battery life.

[0005] Silicon (Si) is the material to succeed graphite as a cathode material. Within the battery's cathode, graphite stores lithium in the form of LiC6 (Li+6C=LiC6), where lithium is surrounded by six carbon atoms, whereas silicon combines with lithium ions to form Li 22 Si5(22Li+5Si=Li 22 It is formed from Si5). In fact, silicon has excellent characteristics with an energy capacity of 4,200 mAh / g, which is about 10 times greater than that of graphite (372 mAh / g). However, silicon-based anode materials have the characteristic of expanding by 300% to 400% during charging and discharging. Consequently, during lithium charging, cracking of the carbon coating layer or delamination from the electrode occurs due to volume expansion, and electrolyte seeps into the cracked carbon gaps, oxidizing the silicon and drastically reducing its lifespan. Accordingly, various studies are being conducted on methods to effectively control the expansion of silicon-based anode active materials.

[0006] When silicon is used as the negative electrode material for lithium-ion batteries, it has the disadvantage of undergoing a volume expansion of 300–400% compared to the initial state during the insertion and extraction of lithium ions while charging and discharging, and the continuous formation of unstable solid electrolyte interfaces (SEIs) on the silicon surface due to the decomposition reaction of the electrolyte. This causes cracks in the electrode, drastically reducing the battery's lifespan characteristics and leading to capacity loss, making commercialization difficult. Many studies are being conducted to overcome these disadvantages of silicon, and a representative method involves manufacturing a composite by mixing silicon with carbon-based materials.

[0007] As such, conventionally, to improve the performance of lithium-ion batteries, a method has been used to manufacture composites by adding carbon-based materials, such as activated carbon (AC), graphene (GR), and carbon nanotubes (MWCNTs), to silicon.

[0008] The background technology related to the present invention is disclosed in Korean Registered Patent Publication No. 10-2185490 (published on Dec. 02, 2020, Title of Invention: Negative electrode material for a non-aqueous electrolyte secondary battery containing a silicon oxide composite and method for manufacturing the same). The problem to be solved

[0010] One objective of the present invention is to provide a negative electrode material for a lithium secondary battery that has excellent durability and structural stability, can uniformly contain silicon within the pores, and possesses high capacity, high power, and long life characteristics when filled with silicon.

[0011] Another objective of the present invention is to provide a negative electrode material for a lithium secondary battery that enables uniform filling of silicon within the pores, facilitates volume change due to the expansion and contraction of silicon during charging and discharging of the negative electrode material, and has excellent effects in preventing an increase in the thickness of the solid electrolyte interphase (SEI) and a reduction in lifespan.

[0012] Another objective of the present invention is to provide a negative electrode material for a lithium secondary battery having uniform electrochemical properties due to excellent uniformity of particle size distribution.

[0013] Another objective of the present invention is to provide a negative electrode material for a lithium secondary battery having excellent electrical conductivity, reversibility, and initial charge efficiency (ICE) characteristics.

[0014] Another objective of the present invention is to provide a negative electrode material for a lithium secondary battery having excellent long-term use stability (cyclability) and charge / discharge (C-rate) efficiency.

[0015] Another objective of the present invention is to provide a negative electrode material for a lithium secondary battery that can be included in a high content during the manufacture of the negative electrode of a lithium secondary battery.

[0016] Another objective of the present invention is to provide a negative electrode material for a lithium secondary battery with excellent productivity and economic efficiency.

[0017] Another objective of the present invention is to provide a method for manufacturing the cathode material.

[0018] Another objective of the present invention is to provide a lithium secondary battery comprising the above-mentioned negative electrode material. means of solving the problem

[0020] One aspect of the present invention relates to a negative electrode material for a lithium secondary battery. In one embodiment, the negative electrode material for a lithium secondary battery comprises: a porous carbon carrier; nanosilicon filled in the pores of the carbon carrier; a first coating layer formed on the outer surface of the carbon carrier; and a second coating layer formed on the outer surface of the first coating layer and having a lower hardness than the first coating layer; wherein the carbon carrier has a higher hardness than the second coating layer, and the negative electrode material has a D-band peak intensity (I) relative to the G-band peak intensity in a Raman spectrum D / I G ) is 1.3 or less.

[0021] In one embodiment, the carbon carrier has a pencil hardness of 1H to 6H and a skeletal density of 0.3 g / cm³ as measured according to ISO 15184. 3 That is all, and the above-mentioned first coating layer has a pencil hardness of 4H or higher and a density of 1.0 g / cm³ as measured in accordance with ISO 15184. 3 It exceeds, and the above-mentioned second coating layer has a pencil hardness of B to 3H and a density of 1.0 g / cm³ as measured in accordance with ISO 15184. 3 It may be less than.

[0022] In one embodiment, the cathode material may comprise 20 to 70 weight% of a carbon carrier, 10 to 70 weight% of nanosilicon, 1 to 30 weight% of a first coating layer, and 1 to 20 weight% of a second coating layer.

[0023] In one embodiment, the nanosilicon has an average particle size of 0.5 to 100 nm, and in the X-ray diffraction spectrum using CuKα rays, it may have effective peaks in the regions where the diffraction angle (2θ) value in the (111) plane is 26 to 30˚ and the diffraction angle (2θ) value in the (220) plane is 47 to 50˚.

[0024] In one embodiment, the nanosilicon may satisfy the following Equation 1 for the X-ray diffraction peak using CuKα rays:

[0025] [Equation 1]

[0026] 3 ≤ IS(111) / IS(220) ≤ 10

[0027] (In the above Equation 1, IS (111) is the maximum peak intensity on the (111) plane of the nanosilicon, and IS (220) is the maximum peak intensity on the (220) plane of the nanosilicon).

[0028] In one embodiment, the carbon carrier comprises tunnel-shaped pores branched from the interior toward the surface, wherein the tunnel-shaped pores can be connected to each other to form a continuous network.

[0029] In one embodiment, the carbon carrier may comprise 60 to 99 volume% of micro pores with a diameter of 2 nm or less and 1 to 40 volume% of meso pores with a diameter greater than 2 nm and less than or equal to 50 nm, based on the total pore volume.

[0030] In one embodiment, the first coating layer may be formed by penetrating at least a portion of the pores of the carbon carrier.

[0031] In one embodiment, the first coating layer may be formed by penetrating into the pores formed on the surface of the carbon carrier to a depth of 0.05 μm or more.

[0032] In one embodiment, the carbon carrier has a full width at half maximum (FWHM) of an X-ray diffraction angle (2θ) using CuKα rays of the (002) plane of 3˚ to 10˚, and the first coating layer may have a full width at half maximum (FWHM) of an X-ray diffraction angle (2θ) using CuKα rays of the (002) plane of 3˚ to 6˚.

[0033] In one embodiment, the first coating layer has an oxygen permeability of 4.0 x 10 -7 Up to 4.0 X 10 -2 It could be darcy.

[0034] In one embodiment, the second coating layer has a 2D-band peak intensity (I) relative to the G-band peak intensity in a Raman spectrum. 2D / IG ) can be 0.35 to 0.85.

[0035] In one embodiment, the carbon carrier may satisfy the following Equation 2 for the X-ray diffraction peak using CuKα rays:

[0036] [Equation 2]

[0037] 5 ≤ I(002) / I(100) ≤ 20

[0038] (In the above Equation 2, I(002) is the maximum peak intensity on the (002) plane of the carbon carrier, and I(100) is the maximum peak intensity on the (100) plane of the carbon carrier).

[0039] In one embodiment, the carbon carrier has a total pore volume of 0.3 to 1.0 cm³ 3 / g, porosity 10–90%, tap density 0.7 g / cm³ 3 Ideal and specific surface area (BET) 1,400–1,800 m² 2 / g, and the above cathode material has a total pore volume of 0.01 cm³ 3 / g or less, tap density 0.8 g / cm³ 3 Ideal and specific surface area (BET) 5m² 2 It may be less than / g.

[0040] In one embodiment, the cathode material has an average particle size of 0.5 to 5 μm and a span value of (D90-D10) / D50 of 2.0 or less.

[0041] Another aspect of the present invention relates to a method for manufacturing a negative electrode material for a lithium secondary battery. In one embodiment, the method for manufacturing a negative electrode material for a lithium secondary battery comprises the steps of: heating and cooling a carbon precursor mixture to produce an intermediate; grinding the intermediate to produce a ground material; activating the ground material with heat treatment; calcining the activated ground material at 900°C or higher to produce a porous calcined material; chemically vaporizing (CVI) a silicon precursor gas into the pores of the calcined material; and heat-treating the calcined material using a hard coating material to produce a composite having a first coating layer formed on the outer surface of the calcined material. The method comprises the step of heat-treating a first mixture including the composite and graphene to form a second coating layer on the outer surface of the composite; wherein the negative electrode material for a lithium secondary battery comprises a porous carbon carrier, nanosilicon filled in the pores of the carbon carrier, a first coating layer formed on the outer surface of the carbon carrier, and a second coating layer formed on the outer surface of the first coating layer and having a lower hardness than the first coating layer, wherein the carbon carrier has a higher hardness than the second coating layer, and the negative electrode material has a D-band peak intensity (I) relative to the G-band peak intensity in a Raman spectrum D / I G ) is 1.3 or less.

[0042] In one embodiment, the first mixture may be heat-treated at 600 to 1100°C to form the second coating layer.

[0043] In one embodiment, the carbon precursor mixture comprises a carbon precursor and a crosslinking agent, wherein the carbon precursor comprises one or more of an organic polymer and an inorganic polymer, wherein the organic polymer comprises one or more of cellulose, celluloid, nylon, polyacrylic, phenolic resin, melamine, polyvinyl chloride, polystyrene, polyethylene, hydrogenated nitrile butadiene rubber (H-NBR), nitrile butadiene rubber (NBR), polyvinylidene fluoride (PVDF), and styrene butadiene rubber (SBR), the inorganic polymer comprises one or more of polysiloxane, polyphosphazene, and polyphosphate, and the crosslinking agent may comprise one or more of urea and amine compounds.

[0044] In one embodiment, the intermediate may be prepared by including the step of heating the carbon precursor mixture to 80 to 250°C and then cooling it to 0°C or lower.

[0045] In one embodiment, the activation heat treatment can be performed at 650 to 1150°C.

[0046] In one embodiment, the calcination may be manufactured by including the step of first calcining the activated pulverized material by heating and maintaining it at 900 to 1100°C at a pressure of 2 to 8 atm; and the step of second calcining the first calcined pulverized material at 1100 to 1700°C at a pressure of 0.5 to 0.8 atm.

[0047] In one embodiment, the silicon precursor gas is silane (SiH4), disilane (Si2H6), trisilane (Si3H8), or tetrasilane (Si4H 10 It may include one or more of ), chlorosilane and methylchlorosilane.

[0048] In one embodiment, the chemical vapor deposition can be carried out at 300 to 900°C.

[0049] In one embodiment, the first coating layer may be formed by including the step of heat-treating the sintered product at 500 to 1200°C using a hard coating material.

[0050] Another aspect of the present invention relates to a lithium secondary battery comprising the above-mentioned cathode material. In one embodiment, the lithium secondary battery comprises a positive electrode; a negative electrode; and an electrolyte formed between the positive electrode and the negative electrode, wherein the negative electrode comprises the above-mentioned cathode material. Effects of the invention

[0052] The negative electrode material for a lithium secondary battery according to the present invention has excellent durability and structural stability, is capable of uniformly containing silicon within the pores, possesses high capacity, high power, and long life characteristics when silicon is filled, allows for uniform silicon filling within the pores, facilitates volume change due to expansion and contraction of silicon during charging and discharging of the negative electrode material, has an excellent effect in preventing an increase in thickness and a decrease in lifespan of the solid electrolyte interphase (SEI), possesses uniform electrochemical characteristics due to excellent uniformity of particle size distribution, has excellent electrical conductivity, reversibility, and initial charge efficiency (ICE) characteristics, has excellent cyclability and C-rate efficiency, and can be included in a high content when manufacturing a lithium secondary battery negative electrode. Brief explanation of the drawing

[0054] FIG. 1 shows a negative electrode material for a lithium secondary battery according to one embodiment of the present invention. FIG. 2 shows a cross-section of a negative electrode material for a lithium secondary battery according to one embodiment of the present invention. Figure 3(a) is a Nyquist plot of the EIS analysis before operation of the secondary batteries of the example and comparative example, and Figure 3(b) is a Nyquist plot of the EIS analysis after 500 cycles of operation of the secondary batteries of the example and comparative example. Figure 4 is a graph showing the change in specific capacity according to the operation of the secondary batteries of the examples and comparative examples. Figure 5 is a graph showing the change in specific capacity according to the operation of the secondary batteries of the examples and comparative examples. Figure 6 is a graph showing the change in specific capacity according to the operation of the secondary batteries of the examples and comparative examples. Specific details for implementing the invention

[0055] In describing the present invention, if it is determined that a detailed description of related known technologies or configurations could unnecessarily obscure the essence of the invention, such detailed description will be omitted.

[0056] Furthermore, the terms described below are defined in consideration of their functions in the present invention; since these may vary depending on the intentions or practices of the user or operator, their definitions should be based on the content throughout this specification describing the present invention.

[0058] Anode material for lithium secondary batteries

[0059] One aspect of the present invention relates to a negative electrode material (or negative electrode material) for a lithium secondary battery. FIG. 1 shows a negative electrode material for a lithium secondary battery according to one embodiment of the present invention, and FIG. 2 shows a cross-section of a negative electrode material for a lithium secondary battery according to one embodiment of the present invention.

[0060] Referring to FIGS. 1 and 2 above, a negative electrode material (100) for a lithium secondary battery comprises: a porous carbon carrier (10); nanosilicon (20) filled in the pores (12) of the carbon carrier (10); a first coating layer (30) formed on the outer surface of the carbon carrier (10); and a second coating layer (40) formed on the outer surface of the first coating layer (30) and having a lower hardness than the first coating layer; wherein the carbon carrier (10) has a higher hardness than the second coating layer (40), and the negative electrode material (100) has a D-band peak intensity (I) relative to the G-band peak intensity in a Raman spectrumD / I G ) is 1.3 or less.

[0061] The above cathode material has a D-band peak intensity (I) relative to the G-band peak intensity in the Raman spectrum. D / I G ) is 1.3 or less. The D-band peak intensity (I) relative to the G-band peak intensity of the above cathode material D / I G If ) exceeds 1.3, carbon carriers may be easily destroyed due to the expansion and contraction of silicon during charging and discharging of the cathode material, which can degrade lifespan and output characteristics. For example, the above cathode material has a D-band peak intensity (I) relative to the G-band peak intensity D / I G ) can be 0.6 to 1.2 or 0.7 to 1.1.

[0063] (1) Carbon carrier

[0064] In one embodiment, the carbon carrier has a D-band of 1,250 to 1,350 cm⁻¹ in the Raman spectrum. -1 Wavenumber range and G-band are 1,550 to 1,650 cm -1 Each can have a peak value within the wavenumber range. Under the above conditions, the carbon carrier exhibits excellent durability, nanosilicon is easily filled inside the pores, volume changes due to the expansion and contraction of nanosilicon during cathode charging and discharging are easily controlled, and output characteristics may be excellent. For example, the carbon carrier has a D-band of 1,280 to 1,320 cm⁻¹ in the Raman spectrum. -1 Wavenumber range and G-band are 1,580 to 1,630 cm -1 Each can have a peak value within the wavenumber range.

[0065] For example, the Raman spectrum of the carbon carrier can be measured using a 532 nm argon (Ar) laser as an excitation source.

[0066] For example, the Raman spectrum of the carbon carrier can be measured using a 532 nm green laser and a 785 nm NIR (Near Infrared) laser as excitation sources.

[0067] Referring to FIGS. 1 and 2 above, the carbon carrier (10) includes tunnel-shaped pores (12) branched from the inside toward the surface, and the tunnel-shaped pores can be connected to each other to form a continuous network. Under the pore conditions, nanosilicon (20) is uniformly filled inside the pores of the carbon carrier, and volume changes due to the expansion and contraction of nanosilicon during charging and discharging of the cathode material can be easily controlled, and output characteristics can be excellent.

[0068] The pores of the carbon carrier may include open pores and closed pores.

[0069] The total volume of open pores in the carbon carrier may be higher than the total volume of closed pores. Under these conditions, nano-silicon filling into the carbon carrier pores is facilitated, increasing the nano-silicon infiltration rate. Consequently, the nano-silicon filling rate within the pores is high, which can increase the charge and discharge capacity of the secondary battery.

[0070] In one embodiment, the pores of the carbon carrier can be analyzed using mercury porosimetry and gas porosimetry. The mercury porosimetry can analyze the pores of the carbon carrier by applying controlled pressure to a carbon carrier sample immersed in mercury having non-wetting properties. Meanwhile, since mercury has a high contact angle, external pressure must be applied for the mercury to penetrate into the pores of the carbon carrier.

[0071] The amount of pressure required for mercury to penetrate into the pores of the carbon carrier is inversely proportional to the pore size. That is, the larger the pore diameter (size), the smaller the amount of pressure required for mercury to penetrate into the pores. A mercury porosimeter can calculate the volume and pore size distribution of the carbon carrier pores from the pressure versus intrusion data generated by the instrument using the known Washburn Equation.

[0072] The above gas porosimetry method can analyze the pores of a carbon carrier using gases such as nitrogen (N2), hydrogen (H2), oxygen (O2), methane (CH4), butane, argon (Ar), and carbon dioxide (CO2). For example, the pores can be analyzed by injecting the above gas into the carbon carrier and measuring the amount of gas adsorbed at different pressures at an isothermal temperature.

[0073] In one embodiment, the carbon carrier has a total pore volume of 0.3 to 1.0 cm³ 3 It may be / g. Under the above total pore volume conditions, silicon is uniformly filled inside the pores of the carbon carrier, and volume changes due to the expansion and contraction of silicon during charging and discharging of the cathode material are easily controlled, and output characteristics may be excellent. For example, the carbon carrier has a total pore volume of 0.3 to 1.0 cm³ 3 / g, 0.3~0.8 cm 3 / g or 0.3–0.5 cm 3 / g can be.

[0074] In one embodiment, the carbon carrier may have a porosity of 10 to 90%. Under the above total porosity conditions, nanosilicon is uniformly filled inside the pores of the carbon carrier, and volume changes due to the expansion and contraction of nanosilicon during charging and discharging of the cathode material can be easily controlled, and output characteristics may be excellent. For example, the carbon carrier may have a porosity of 15 to 85%, 20 to 70%, or 25 to 65%.

[0075] The total pore volume and porosity of the above carbon carrier can be analyzed using the mercury porosity measurement method and the nitrogen adsorption method.

[0076] In one embodiment, the carbon carrier may comprise 60 to 99 volume% of micro pores with a diameter of 2 nm or less and 1 to 40 volume% of meso pores with a diameter greater than 2 nm and less than 50 nm, based on the total pore volume. Under the above conditions, the carbon carrier may have excellent durability, nanosilicon may easily penetrate and fill into the pores, have an excellent effect in buffering volume changes due to the expansion and contraction of nanosilicon during charging and discharging of the cathode material, and have excellent output characteristics.

[0077] For example, the above micropores may have a diameter greater than 0 and less than or equal to 2 nm.

[0078] The above micropores and mesopores may each be in the form of open pores or closed pores.

[0079] In one embodiment, the carbon carrier may comprise 60 to 99 volume% of micro pores with a diameter of 2 nm or less relative to the total pore volume. Under the above conditions, the carbon carrier may have excellent durability, excellent buffering effect against volume changes due to the expansion and contraction of nanosilicon during charging and discharging of the cathode material, and excellent output characteristics. For example, it may comprise 70 to 99 volume%, 75 to 99 volume%, or 77 to 97 volume% of micro pores with a diameter greater than 0 and less than or equal to 2 nm.

[0080] In one embodiment, the carbon carrier may contain 1 to 40 volume% of meso pores with a diameter greater than 2 nm and less than or equal to 50 nm, based on the total pore volume. Under these conditions, the carbon carrier may have excellent durability, nanosilicon may easily penetrate and fill into the pores, have an excellent effect in buffering volume changes due to the expansion and contraction of nanosilicon during charging and discharging of the cathode material, and have excellent output characteristics. For example, it may contain 1 to 30 volume%, 1 to 25 volume%, or 5 to 20 volume% of meso pores with a diameter greater than 2 nm and less than or equal to 50 nm.

[0081] The above carbon carrier may further form macropores. For example, the macropores may have a diameter greater than 50 nm, a diameter greater than 50 nm and less than or equal to 200 nm, or a diameter greater than 50 nm and less than or equal to 100 nm.

[0082] The above macropores may be in the form of open pores or closed pores.

[0083] In one embodiment, the carbon carrier may further include 1 to 15 volume percent of macro pores with a diameter greater than 50 nm with respect to the total pore volume. Under these conditions, nanosilicon can easily penetrate and fill the pores without reducing the durability of the carbon carrier, and excellent output characteristics may be achieved. For example, it may include 1 to 10 volume percent, 1 to 8 volume percent, or 1 to 6 volume percent of macro pores with a diameter greater than 50 nm.

[0084] At this time, the micropores, mesopores, and macropores of the carbon carrier can be analyzed using the gas porosity measurement method.

[0085] In addition, the mesopores and macropores of the carbon carrier can be analyzed using the mercury porosity measurement method.

[0086] For example, the micropores, mesopores, and macropores of the carbon carrier can be measured using one or more of Microtrac’s BELSORP MAX X product and Micromeritics’ MicroActive AutoPore V 9600 Version product.

[0087] In one embodiment, the carbon carrier has a specific surface area (BET) of 1,400 to 1,800 m² 2 It may be / g. Under the above specific surface area conditions, structural stability is excellent, space for silicon filling in the pores can be secured, volume changes due to silicon expansion and contraction can be easily controlled, and high power and long life characteristics may be excellent. For example, a specific surface area (BET) of 1,500–1,800 m² 2 / g can be.

[0088] In one embodiment, the carbon carrier has a skeletal density of 0.3 g / cm³ 3 It may be the above. Under the above framework density conditions, lightness and structural stability are excellent, the uniformity of the carbon carrier is excellent, the electrode packing density can be increased, and the lifespan characteristics can be excellent. For example, the carbon carrier has a framework density of 0.3 to 3.0 g / cm³ 3 It could be.

[0089] In one embodiment, the carbon carrier has a tap density of 0.7 g / cm³ 3 It may be above. Under the above tap density conditions, lightness and structural stability are excellent, carbon carrier uniformity is excellent, electrode packing density can be increased, and lifespan characteristics can be excellent. For example, the above carbon carrier has a tap density of 0.8 to 3 g / cm³ 3 or 1.0~1.5 g / cm³ 3 It could be.

[0090] In one embodiment, the carbon carrier may have an electrical resistance of 100 μΩ·m or less. For example, the carbon carrier may have an electrical resistance of 5 to 100 μΩ·m.

[0091] In one embodiment, the carbon carrier may have a pencil hardness of 1H to 6H as measured according to ISO 15184. Under these conditions, the carbon carrier may have excellent durability, easily control volume changes due to the expansion and contraction of silicon during charging and discharging of the cathode material, and exhibit excellent high power and long life characteristics. For example, the carbon carrier may have a pencil hardness of 2H to 5H as measured according to ISO 15184.

[0092] In one embodiment, the carbon carrier may have an average particle size of 5 to 20 μm. Under these conditions, the carbon carrier may have excellent durability, silicon may be easily filled inside the pores, volume changes due to expansion and contraction of silicon during charging and discharging of the cathode material may be easily controlled, and high power and long life characteristics may be excellent. For example, the carbon carrier may have an average particle size of 5 to 18 μm, 5 to 15 μm, or 5 to 10 μm.

[0093] In one embodiment, the carbon carrier may have a span value of (D90-D10) / D50 of 2.0 or less. Meanwhile, D90, D50, and D10 each represent particle sizes corresponding to 90%, 50%, and 10% of the maximum value in the total particle size (diameter) distribution calculated from the volume of the carbon carrier. Under the above conditions, the uniformity of the particle size distribution is excellent, so uniform electrochemical properties can be obtained. For example, the carbon carrier may have a span value of (D90-D10) / D50 of 2 or less, 1.5 or less, 1.0 to 2.0, or 1.0 to 1.5.

[0094] In one embodiment, the carbon carrier has a gas permeability of 30 to 100 cc / m² measured under pressure conditions of 0.1 to 1 kPa according to ASTM D 1434. 2·day may be possible. Under the above conditions, the carbon carrier has excellent durability, silicon is easily filled inside the pores, volume changes due to the expansion and contraction of silicon during charging and discharging of the cathode material are easily controlled, and high power and long life characteristics may be excellent. For example, the carbon carrier has the above gas permeability 30~80 cc / m 2 · day or 30~60 cc / m 2 · It can be a day.

[0095] For example, the above gas permeability can be measured using the differential pressure method. The differential pressure method can be performed using a measuring facility comprising: a chamber; a support formed inside the chamber that divides the chamber into an upper chamber and a lower chamber and on which a carbon carrier specimen is placed; a vacuum pump that reduces the pressure inside the chamber; an injection line provided in the upper chamber for injecting a test gas; and a pressure gauge for measuring the internal pressure of the chamber.

[0096] For example, the upper and lower surfaces of the support member of the measuring equipment are each formed of a porous filter, and a sealing means such as an O-ring is formed on the upper surface of the support member so that only the porous filter is exposed on the upper surface of the support member. The porous filter may be a conventional type. For example, it may include sintered porous ceramic or porous metal, but is not limited thereto.

[0097] Specifically, the above differential pressure method places the carbon carrier specimen between the upper chamber and the lower chamber, evacuates the inside of the chamber using a vacuum pump, and then injects a test gas under atmospheric pressure conditions into the upper chamber to form a constant pressure difference between the upper chamber and the lower chamber. Due to the pressure difference, the gas permeates from the upper chamber to the lower chamber through the filter of the support member, and the gas permeability of the carbon carrier specimen can be measured by measuring the pressure change in the lower chamber with a pressure gauge.

[0098] For example, the gas permeability of the above carbon carrier can be measured using GBPI’s N500L product.

[0099] In one embodiment, the carbon carrier may have a full width at half maximum (FWHM) of 3° to 10° at an X-ray diffraction angle (2θ) using CuKα lines of the (002) plane. Within the above range of full width at half maximum, the carbon carrier can have high hardness, excellent durability, and high capacity and high power characteristics. For example, the carbon carrier may have a full width at half maximum of 3 to 8° or 3 to 7°. For example, the carbon carrier may have a full width at half maximum of 3° to 10° at an X-ray diffraction (XRD) spectrum measured with a step size of 0.01° using CuKα lines of 1.54178 Å and 2θ of 10-70°.

[0100] In one embodiment, the carbon carrier may satisfy the following Equation 2 for the X-ray diffraction peak using CuKα rays:

[0101] [Equation 2]

[0102] 5 ≤ I(002) / I(100) ≤ 20

[0103] (In the above Equation 2, I(002) is the maximum peak intensity on the (002) plane of the carbon carrier, and I(100) is the maximum peak intensity on the (100) plane of the carbon carrier).

[0104] When the conditions of Equation 1 above are satisfied, the carbon carrier can have high hardness, excellent durability, and high capacity and high output characteristics. For example, the carbon carrier may have I(002) / I(100) of Equation 1 as 5 to 18, 6 to 15, or 7 to 12.

[0105] The porous carbon carrier according to the present invention can form a composite by evenly filling the pores with nanosilicon. In addition, by heat-treating the surface of the composite with carbon having excellent crystallinity to control volume changes due to the expansion and contraction of nanosilicon, the lifespan and efficiency of the secondary battery are increased, the electrical capacity is increased, and the electrical conductivity is increased, thereby improving the rate characteristics of the battery. Furthermore, the density of the carbon layer is increased, and the thickness of the SEI (Solid Electrolyte Layer) caused by the expansion of nanosilicon is increased, thereby improving the performance of the secondary battery by mitigating the reduction in efficiency and lifespan.

[0106] In one embodiment, the carbon carrier may be included in an amount of 20 to 70 weight percent based on the total weight of the cathode material. Under these conditions, the durability and lightness of the cathode material are excellent, and the effect of buffering volume changes caused by the expansion and contraction of nanosilicon during charging and discharging of the secondary battery may be excellent. For example, the carbon carrier may be included in an amount of 30 to 70 weight percent, 35 to 65 weight percent, 35 to 60 weight percent, or 35 to 55 weight percent based on the total weight of the cathode material.

[0108] (2) Nanosilicon

[0109] The above nanosilicon may be included to secure high capacity and high power characteristics. In one embodiment, the nanosilicon may be spherical, polyhedral, elliptical, or irregular. For example, it may be spherical.

[0110] In one embodiment, the nanosilicon may be crystalline. Under these conditions, high capacity and high power characteristics can be secured.

[0111] In one embodiment, the nanosilicon may have an average particle size of 0.5 to 100 nm. Under these conditions, high capacity and high power characteristics of the nanosilicon are secured, it can be easily filled into the pores, and the long lifespan effect may be excellent. For example, the nanosilicon may have an average particle size of 0.5 to 80 nm, 1 to 60 nm, 2 to 40 nm, or 15 to 30 nm.

[0112] In one embodiment, the nanosilicon may have effective peaks in the region where the diffraction angle (2θ) value in the (111) plane is 26 to 30˚ and the diffraction angle (2θ) value in the (220) plane is 47 to 50˚, respectively, in the X-ray diffraction spectrum using CuKα rays. Under these conditions, high capacity and high power characteristics of the nanosilicon are secured, and the phenomenon of silicon particle breakage during charging and discharging can be significantly reduced.

[0113] For example, the nanosilicon may have effective peaks in the region where the diffraction angle (2θ) value in the (111) plane is 27 to 28˚ and the diffraction angle (2θ) value in the (220) plane is 48 to 50˚, respectively, in an X-ray diffraction (XRD) spectrum using CuKα rays of 1.54 to 2.0 Å.

[0114] In one embodiment, the nanosilicon may have a full width at half maximum (FWHM) of the X-ray diffraction angle (2θ) using CuKα lines of the (111) and (220) planes, each of 0.4˚ to 0.8˚. Under these conditions, high capacity and high power characteristics of the nanosilicon are secured, and the breakage of silicon particles during charging and discharging can be significantly reduced.

[0115] For example, the above nanosilicon may have a full width at half maximum (FWHM) of the X-ray diffraction angle (2θ) using CuKα rays of 1.54 to 2.0 Å in the (111) and (220) planes, each of which is 0.5˚ to 0.7˚.

[0116] In one embodiment, the nanosilicon may satisfy the following Equation 1 for the X-ray diffraction peak using CuKα rays:

[0117] [Equation 1]

[0118] 3 ≤ IS(111) / IS(220) ≤ 10

[0119] (In the above Equation 1, IS (111) is the maximum peak intensity on the (111) plane of the nanosilicon, and IS (220) is the maximum peak intensity on the (220) plane of the nanosilicon).

[0120] When the conditions of Equation 1 above are satisfied, high capacity and high power characteristics of the nanosilicon are secured, and the phenomenon of silicon particle breakage during charging and discharging can be significantly reduced. For example, the value of Equation 1 above may be 3 to 8 or 3 to 7.

[0121] In one embodiment, the nanosilicon may be included in an amount of 10 to 70 weight% based on the total weight of the cathode material. Under these conditions, the cathode material may have excellent durability and excellent high capacity and high power characteristics. For example, the nanosilicon may be included in an amount of 20 to 65 weight%, 30 to 60 weight%, 35 to 55 weight%, or 35 to 50 weight% based on the total weight of the cathode material.

[0123] (3) First coating layer

[0124] When the first coating layer is formed, the strength and durability of the cathode material are excellent, preventing cracking or destruction of the cathode material during the expansion of nanosilicon, preventing an increase in the thickness of the Solid Electrolyte Interface (SEI) on the outer surface of the cathode material, preventing capacity degradation, and allowing for excellent electrical conductivity and long life characteristics.

[0125] In one embodiment, the first coating layer may have a thickness of 50 to 3000 nm. When formed with the above thickness, the durability and structural stability of the cathode material are excellent, damage to the cathode material due to charging and discharging is prevented, and long life characteristics, high power output, and electrical characteristics may be excellent. For example, the first coating layer may have a thickness of 50 to 2000 nm, 100 to 2000 nm, or 500 to 1500 nm.

[0126] FIG. 2 above shows a cross-section of a cathode material according to one embodiment of the present invention. Referring to FIG. 2, the first coating layer (30) may be formed by penetrating at least a portion of the pores (12) of the carbon carrier (10). For example, the first coating layer may be formed by penetrating the outer surface of the carbon carrier and the space inside the carbon carrier pores that is not filled with the nanosilicon. Under these conditions, cracking or damage to the cathode material due to the expansion of the nanosilicon can be prevented.

[0127] In one embodiment, the first coating layer may be formed by penetrating into the pores formed on the surface of the carbon carrier to a depth of 0.05 μm or more. Referring to FIG. 2, the penetration depth (D) of the first coating layer may refer to a distance measured in the vertical direction relative to the surface of the carbon carrier. When the first coating layer is formed by penetrating into the pores on the surface of the carbon carrier as described above, it prevents cracking or damage to the cathode material caused by the expansion of the nanosilicon, and may exhibit excellent electrical conductivity and long life characteristics. For example, the first coating layer may be formed by penetrating into the pores on the surface of the carbon carrier to a depth of 0.1 to 2 μm or 0.3 to 1.5 μm.

[0128] In one embodiment, the penetration depth of the first coating layer can be measured using a field emission scanning electron microscope (FESEM) to determine the pore penetration depth of the first coating layer relative to the surface of the carbon carrier.

[0129] In one embodiment, the first coating layer has a density of 1.0 g / cm³ 3 It may exceed. Under the above conditions, lightness and structural stability may be excellent. For example, the first coating layer has a density of 1.1 to 2.1 g / cm³ 3 or 1.3~2.1 g / cm³ 3 It could be.

[0130] In one embodiment, the first coating layer has a specific surface area (BET) of 100 m² 2 It may be less than / g. Under the above conditions, structural stability may be excellent.

[0131] In one sphere, the first coating layer may have a pencil hardness of 4H or higher as measured according to ISO 15184. Under the above conditions, volume changes due to the expansion and contraction of nanosilicon during charging and discharging of the cathode material can be easily controlled, and electrical characteristics such as electrical conductivity, high power output, and long lifespan characteristics may be excellent. For example, the first coating layer may have a pencil hardness of 4.5H to 7H or 5H to 7H as measured according to ISO 15184.

[0132] For example, the first coating layer may have a higher pencil hardness than the carbon carrier. Under the above conditions, volume changes due to the expansion and contraction of nanosilicon during charging and discharging of the cathode material can be easily controlled, and high power output and long lifespan characteristics may be excellent.

[0133] In one embodiment, the first coating layer may have an electrical resistance (resistivity) of 5 μΩ·m or less. Under the above conditions, electrical properties such as electrical conductivity may be excellent. For example, the first coating layer may have an electrical resistance of 0.01 to 5 μΩ·m.

[0134] In one embodiment, the first coating layer has an oxygen permeability of 4.0 x 10 -7 Up to 4.0 X 10 -2 It may be darcy. Under the above conditions, it may exhibit excellent gas impermeability and durability, excellent durability and structural stability of the cathode material, fire prevention effect at high temperatures, easy control of volume changes due to the expansion and contraction of nanosilicon during charging and discharging, and excellent high power and long life characteristics. For example, the first coating layer has an oxygen permeability of 4.0 x 10 -6 Up to 4.0 X 10 -2 darcy, or 4.0 X 10-6 Up to 4.0 X 10 -3 It could be darcy.

[0135] In one embodiment, the oxygen gas transmission rate (OTR) of the first coating layer can be measured by a known method in accordance with ASTM D3985 or JIS K7126 standards. For example, the oxygen transmission rate of the first coating layer can be determined by expressing the accumulated amount (volume) of oxygen gas passing through the cathode material due to differential pressure as a function of time, and using this to measure the oxygen transmission coefficient and transmission rate.

[0136] The oxygen permeability of the first coating layer can be measured using MOCON’s products OX-TRAN 2 / 21 MD and OX-TRAN Model 2 / 61, etc.

[0137] In one sphere, the first coating layer may have a full width at half maximum (FWHM) of 3° to 6° at an X-ray diffraction angle (2θ) using CuKα rays of the (002) plane. Within the full width at half maximum range, the first coating layer has high hardness, excellent durability, prevents damage to the cathode material during charging and discharging, and can secure high capacity and high power characteristics. For example, the first coating layer may have a full width at half maximum of 3.5 to 6° or 3.5 to 5.5°. For example, the first coating layer may have a full width at half maximum of 3° to 6° at an X-ray diffraction (XRD) spectrum measured at 2θ of 10-70° with a step size of 0.01° using CuKα rays of 1.54178 Å.

[0138] In one embodiment, the first coating layer may be included in an amount of 1 to 30 weight% with respect to the total weight of the cathode material. When included within this weight range, the durability and structural stability of the cathode material are excellent, and the long lifespan characteristics, high power output, and electrical characteristics may be excellent. For example, the first coating layer may be included in an amount of 1 to 20 weight%, 1 to 15 weight%, 1 to 10 weight%, 1 to 8 weight%, 2 to 8 weight%, or 2 to 5 weight% with respect to the total weight of the cathode material.

[0140] (4) Second coating layer

[0141] When the above second coating layer is formed, cracking or destruction of the cathode material due to the expansion of nanosilicon during charging and discharging of the cathode material is prevented, capacity degradation is prevented, and excellent electrical conductivity and long lifespan characteristics can be achieved.

[0142] In one embodiment, the first coating layer may have a thickness of 50 to 2000 nm. When formed with the above thickness, the durability and structural stability of the cathode material are excellent, damage to the cathode material due to charging and discharging is prevented, and long life characteristics, high power output, and electrical characteristics may be excellent. For example, the second coating layer may have a thickness of 50 to 1500 nm, 100 to 1200 nm, or 500 to 1200 nm.

[0143] In one embodiment, the second coating layer may have a pencil hardness of B to 3H according to ISO 15184 standards. Under the above conditions, when charging and discharging the cathode material, the effect of buffering the expansion of the first coating layer is excellent, thereby preventing cracking or damage to the cathode material and thus providing excellent long-life characteristics. For example, the second coating layer may have a pencil hardness of B to 1.5H or B to 1H.

[0144] In one embodiment, the second coating layer may have an electrical resistance (resistivity) of 10 μΩ·m or more. Under the above conditions, the electrical conductivity of the cathode material may be excellent. For example, the electrical resistance may be 10 to 300 μΩ·m.

[0145] In one embodiment, the second coating layer has a density of 1.0 g / cm³ 3 It may be less than or equal to the above. Under the above conditions, lightness and structural stability may be excellent. For example, the second coating layer has a density of 0.1 to 1.0 g / cm³. 3 , 0.3~1.0g / cm 3 or 0.3~0.7 g / cm² 3 It could be.

[0146] In one embodiment, the first coating layer has a higher pencil hardness than the second coating layer. Under these conditions, when charging and discharging the cathode material, the first coating layer has an excellent buffering effect on the expansion, thereby preventing cracking or damage to the cathode material and allowing for excellent long-life characteristics. If the first coating layer has lower hardness than the second coating layer, cracking or damage to the carbon carrier or cathode material increases during charging and discharging, which may degrade electrochemical characteristics and lifespan characteristics.

[0147] In one embodiment, the carbon carrier has a higher hardness than the second coating layer. If the second coating layer has a higher hardness than the carbon carrier, cracking or damage to the carbon carrier or the cathode material during charging and discharging may increase, thereby degrading electrochemical properties and lifespan characteristics.

[0148] In one embodiment, the second coating layer has a 2D-band peak intensity (I) relative to the G (1G)-band peak intensity in a Raman spectrum. 2D / I G ) may be 0.35 to 0.85. Under the above conditions, the second coating layer has excellent durability and excellent electrical conductivity, thereby enabling high capacity and high power characteristics of the cathode material. For example, the second coating layer has a 2D-band peak intensity (I) relative to the G-band peak intensity in the Raman spectrum. 2D / I G ) can be 0.35~0.80 or 0.35~0.75.

[0149] For example, the 1G band peak of the second coating layer above, measured with a 532 nm excitation CW laser in the Raman spectrum, is 1560–1650 cm⁻¹. -1 It appears in the wavenumber range, with a 1D-band peak at 2600–2850 cm⁻¹ -1 It may appear in the wavenumber range.

[0150] In one embodiment, the second coating layer has a Raman shift of the 2D-band measured with a 532 nm excitation CW laser in the Raman spectrum of 2680–2750 cm⁻¹ -1 It can have a peak value in the wavenumber range. Under the above conditions, the electrical resistance of the second coating layer is minimized, electrical conductivity and high power characteristics are excellent, capacity degradation is prevented, and long life characteristics are excellent.

[0151] In one embodiment, the second coating layer may be included in an amount of 1 to 20 weight percent based on the total weight of the cathode material. When included within this weight range, the durability and structural stability of the cathode material are excellent, preventing damage to the cathode material during charging and discharging, and may exhibit excellent long life characteristics, high power output, and electrical characteristics. For example, the second coating layer may be included in an amount of 1 to 18 weight percent, 1 to 15 weight percent, 1 to 10 weight percent, 1 to 8 weight percent, 2 to 8 weight percent, or 2 to 5 weight percent based on the total weight of the cathode material.

[0152] In one embodiment, the cathode material may include the second coating layer and the first coating layer in a weight ratio of 1:0.5 to 1:6. Under these conditions, the durability and structural stability of the cathode material are excellent, preventing damage to the cathode material during charging and discharging, and may exhibit excellent long life characteristics, high power output, and electrical characteristics. For example, the cathode material may include the second coating layer and the first coating layer in a weight ratio of 1:1 to 1:6, 1:1.5 to 1:5, or 1:2 to 1:4.

[0153] In one embodiment, the cathode material may have an average particle size of 0.5 to 20 μm. Under the above conditions, the cathode material may have excellent durability and excellent high power and long life characteristics. For example, the cathode material may have an average particle size of 0.5 to 20 μm, 0.5 to 18 μm, or 3 to 16 μm.

[0154] In one embodiment, the cathode material has a total pore volume of 0.01 cm³ 3 It may be less than / g. Under the total pore volume conditions of the above cathode material, silicon is uniformly filled inside the pores of the carbon carrier, and volume changes due to the expansion and contraction of silicon during charging and discharging of the cathode material are easily controlled, and output characteristics may be excellent. For example, the above cathode material has a total pore volume of 0.001 to 0.01 cm³ 3 / g, 0.001~0.009 cm 3 / g or 0.003–0.007 cm 3 / g can be.

[0155] In one embodiment, the cathode material has a gas permeability of 0.2 to 1.0 cc / m 2 ·day may be used. Under the above conditions, the cathode material may have excellent durability, easily control volume changes due to the expansion and contraction of silicon during charging and discharging, and exhibit excellent high power and long life characteristics. For example, the cathode material may have a gas permeability of 0.3 to 1.0 cc / m 2 ·day, 0.4~0.9 cc / m 2 day or 0.4~0.8 cc / m 2 · It can be a day.

[0156] In one embodiment, the cathode material has a specific surface area (BET) of 5 m² 2 It may be less than / g. Under the above specific surface area conditions, structural stability is excellent, space for silicon filling in the pores can be secured, volume changes due to silicon expansion and contraction can be easily controlled, and high power and long life characteristics may be excellent. For example, a specific surface area (BET) of 0.5 to 10 m²2 / g, 0.5~5 m 2 / g or 1~4 m 2 It can be / g.

[0157] In one embodiment, the cathode material may have a span value of (D90-D10) / D50 of 2.0 or less. Meanwhile, D90, D50, and D10 each represent particle sizes corresponding to 90%, 50%, and 10% of the maximum value in the total particle size (diameter) distribution calculated from the volume of the cathode material. Under the above conditions, the uniformity of the particle size distribution is excellent, so uniform electrochemical properties can be obtained. For example, the cathode material may have a span value of (D90-D10) / D50 of 2 or less, 1.5 or less, 1.0 to 2.0, or 1.0 to 1.5.

[0158] In one embodiment, the cathode material has a tap density of 0.8 g / cm³ 3 It may be above. Under the above tap density conditions, lightness and structural stability are excellent, carbon carrier uniformity is excellent, electrode packing density can be increased, and lifespan characteristics can be excellent. For example, the above cathode material has a tap density of 0.8 to 3 g / cm³ 3 or 1.0~1.5 g / cm³ 3 It could be.

[0159] In one embodiment, the cathode material may have an electrical resistance of 100 μΩ·m or less. For example, the cathode material may have an electrical resistance of 5 to 100 μΩ·m.

[0161] Method for manufacturing a negative electrode material for a lithium secondary battery

[0162] Another aspect of the present invention relates to a method for manufacturing a negative electrode material for a lithium secondary battery. In one embodiment, the method for manufacturing a negative electrode material for a lithium secondary battery (or a negative electrode material manufacturing method) comprises: (S10) a step of manufacturing an intermediate; (S20) a step of manufacturing a pulverized material; (S30) an activation heat treatment step; (S40) a calcination step; (S50) a chemical vapor deposition step; (S60) a step of forming a first coating layer; and (S70) a step of forming a second coating layer.

[0163] More specifically, the above method for manufacturing a cathode material comprises: (S10) a step of preparing an intermediate by heating and cooling a carbon precursor mixture; (S20) a step of preparing a crushed material by crushing the intermediate; (S30) a step of activating the crushed material through heat treatment; (S40) a step of preparing a porous sintered material by calcining the activated crushed material at 900°C or higher; (S50) a step of chemically vaporizing (CVI) silicon precursor gas into the pores of the sintered material; (S60) a step of preparing a composite in which a first coating layer is formed on the outer surface of the sintered material by heat-treating the sintered material using a hard coating material; and (S70) a step of forming a second coating layer on the outer surface of the composite by heat-treating a first mixture containing the composite and graphene.

[0164] The negative electrode material for a lithium secondary battery manufactured above comprises a porous carbon carrier, nanosilicon filled in the pores of the carbon carrier, a first coating layer formed on the outer surface of the carbon carrier, and a second coating layer formed on the outer surface of the first coating layer and having a lower hardness than the first coating layer.

[0165] The above cathode material has a D-band peak intensity (I) relative to the G-band peak intensity in the Raman spectrum. D / I G ) is 1.3 or less. The D-band peak intensity (I) relative to the G-band peak intensity of the above cathode material D / IG If ) exceeds 1.3, carbon carriers may be easily destroyed due to the expansion and contraction of silicon during charging and discharging of the cathode material, which can degrade lifespan and output characteristics. For example, the above cathode material has a D-band peak intensity (I) relative to the G-band peak intensity D / I G ) can be 0.6 to 1.2 or 0.7 to 1.1.

[0166] In one embodiment, the carbon carrier has a higher hardness than the second coating layer. If the second coating layer has a higher hardness than the carbon carrier, cracking or damage to the carbon carrier or the cathode material during charging and discharging may increase, thereby degrading electrochemical properties and lifespan characteristics.

[0168] (S10) Intermediate manufacturing step

[0169] The above step is to prepare an intermediate by heating and cooling a carbon precursor mixture.

[0170] In one embodiment, the carbon precursor mixture may include a carbon precursor and a crosslinking agent.

[0171] The above carbon precursor may include one or more of organic polymers and inorganic polymers.

[0172] In one embodiment, the organic polymer may include one or more of cellulose, celluloid, nylon, polyacrylic, phenolic resin, melamine, polyvinyl chloride, polystyrene, polyethylene, hydrogenated nitrile butadiene rubber (H-NBR), nitrile butadiene rubber (NBR), polyvinylidene fluoride (PVDF), and styrene butadiene rubber (SBR). When the organic polymer is included, a porous carbon carrier is easily formed, and the durability and mechanical properties of the carbon carrier may be excellent.

[0173] In one embodiment, the organic polymer may comprise the phenol resin and polystyrene in a weight ratio of 1:1 to 1:5. Under these conditions, the durability and mechanical properties of the carbon carrier may be excellent. For example, the organic polymer may comprise the phenol resin and polystyrene in a weight ratio of 1:1.5 to 1:4 or 1:2 to 1:4.

[0174] In one embodiment, the inorganic polymer may include one or more of polysiloxane, polyphosphazene, and polyphosphate. When the inorganic polymer is included, a porous carbon carrier is easily formed, and the durability and mechanical properties of the carbon carrier may be excellent.

[0175] In one embodiment, the carbon precursor may comprise an inorganic polymer and an organic polymer in a weight ratio of 1:0.5 to 1:6. Under these conditions, a porous carbon carrier is easily formed, and the durability and mechanical properties of the carbon carrier may be excellent. For example, the carbon precursor may comprise the inorganic polymer and the organic polymer in a weight ratio of 1:1 to 1:5 or 1:2 to 1:5.

[0176] The above crosslinking agent may include one or more of urea and amine-based compounds. When the above type of crosslinking agent is included, the carbon precursor mixture is easily crosslinked to easily form a porous carbon carrier, and the durability and mechanical properties of the carbon carrier may be excellent.

[0177] The above amine-based compounds may include one or more of ethanolamine, diethanolamine, methyldiethanolamine, phenyldiethanolamine, triethanolamine, pentaerythritol, diethyltoluenediamine, and dimethylthiotoluenediamine.

[0178] When the above amine-based compound is included, the carbon precursor mixture is easily crosslinked, and the durability and mechanical properties of the carbon carrier can be excellent.

[0179] In one embodiment, the carbon precursor mixture may further include a dispersion solvent. The dispersion solvent may include one or more of water, alcohol-based solvents, amide-based solvents, ester-based solvents, and hydrocarbon-based solvents. When the dispersion solvent is included, dispersibility and workability may be excellent.

[0180] For example, the above alcohol-based solvent may include one or more of methanol, ethanol, isopropanol, and butanol. For example, the above amide-based solvent may include one or more of N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAC), and dimethylformamide (DMF). For example, the above hydrocarbon-based solvent may include one or more of toluene and xylene.

[0181] In one embodiment, the carbon precursor mixture may comprise 60 to 80 weight% of a carbon precursor, 10 to 35 weight% of a crosslinking agent, and 1 to 15 weight% of a dispersion solvent.

[0182] In one embodiment, the carbon precursor may be included in an amount of 60 to 80 weight percent based on the total weight of the carbon precursor mixture. When included within this range, the mixability and dispersibility of the carbon precursor mixture are excellent, and the durability and mechanical properties of the carbon carrier may be excellent.

[0183] In one embodiment, the crosslinking agent may be included in an amount of 10 to 35 weight percent based on the total weight of the carbon precursor mixture. When included within this range, the mixability and dispersibility of the carbon precursor mixture are excellent, the pore size and pore distribution conditions of the carbon carrier can be easily controlled, and the durability and mechanical properties may be excellent.

[0184] In one embodiment, the dispersion solvent may be included in an amount of 1 to 15 weight percent based on the total weight of the carbon precursor mixture. When included within this range, the mixability and dispersibility of the carbon precursor mixture are excellent, and the moldability may be excellent.

[0185] In one embodiment, the intermediate may be prepared by including the step of heating the carbon precursor mixture to 80 to 250°C and then cooling it to 0°C or lower. When heated under the above conditions, a gel-like mixture is formed from the carbon precursor mixture, and when cooled under the above conditions, the mixture is easily cooled so that a solid intermediate can be easily formed. For example, the cooling may cool the heated carbon precursor mixture to -5°C to -40°C.

[0187] (S20) Grinding step

[0188] The above step is a step of grinding the intermediate to produce a ground material. When producing the ground material, it is easy to control the particle size of the carbon carrier.

[0189] For example, the above-mentioned ground material can be prepared as a ground mixture comprising one or more intermediates of different types.

[0191] (S30) Activation heat treatment step

[0192] The above step is a step of activating the pulverized material through heat treatment.

[0193] In one embodiment, the activation heat treatment may be performed at 650 to 1150°C. Under these conditions, pores are easily formed inside the carbon carrier, the surface area increases, and the mechanical properties may be excellent.

[0194] The above activation heat treatment can be performed under activation gas conditions. The activation gas may include one or more of carbon dioxide and steam. Under these conditions, pores are easily formed inside the carbon carrier, the surface area increases, and mechanical properties can be excellent.

[0196] (S40) Sintering stage

[0197] The above step is to manufacture a porous sintered product (carbon carrier) by sintering the activated pulverized material at 900°C or higher. If the sintering is performed at a temperature below 900°C, pores are not easily formed inside the carbon carrier, and durability and mechanical properties are degraded. Consequently, the carbon carrier may be easily destroyed due to the expansion and contraction of silicon during charging and discharging of the cathode material, which may lead to a decrease in lifespan and output characteristics. For example, the sintering can be performed at 900 to 2000°C or 900 to 1800°C.

[0198] The above calcination can be carried out under inert gas conditions. For example, the inert gas may include one or more of nitrogen and argon.

[0199] In one embodiment, the calcination may be manufactured by including: a step of first calcining the activated pulverized material by heating and maintaining it at 900 to 1100°C at a pressure of 2 to 8 atm; and a step of second calcining the first calcined pulverized material at 1100 to 1700°C at a pressure of 0.5 to 0.8 atm. When the first and second calcinations are performed under the above conditions, pores are easily formed inside the carbon carrier, and the durability is excellent, so the effect of buffering the expansion and contraction of silicon during charging and discharging of the cathode material is excellent, and high power characteristics and long life characteristics may be excellent.

[0200] The above first and second calcination can be carried out under inert gas conditions. For example, the inert gas may include one or more of nitrogen and argon.

[0201] The above first firing can be carried out at a pressure of 2 to 8 atm. Under these conditions, pores can be easily formed inside the carbon carrier, and durability can be excellent. For example, the above first firing can be carried out at 2 to 6 atm or 3 to 5 atm.

[0202] The above secondary firing can be performed at a pressure of 0.5 to 0.8 atm. Under these conditions, pores are easily formed inside the carbon carrier, durability is excellent, and uniformity of particle size distribution is excellent, allowing for uniform electrochemical properties. For example, the above secondary firing can be performed at 0.5 to 0.7 atm.

[0204] (S50) Chemical vapor deposition stage

[0205] The step is to chemically deposit silicon precursor gas (CVI) into the pores of the above-mentioned calcined product.

[0206] In one embodiment, the silicon precursor gas is silane (SiH4), disilane (Si2H6), trisilane (Si3H8), or tetrasilane (Si4H 10 It may include one or more of ), chlorosilane and methylchlorosilane. When the silicon precursor gas is applied, the silicon precursor gas is easily deposited inside the pores of the calcined product, allowing nanosilicon to be easily filled.

[0207] For example, the above methylchlorosilane may include one or more of methyltrichlorosilane (CH3SiCl3) and dimethyldichlorosilane ((CH3)2SiCl2).

[0208] In one embodiment, the chemical vapor deposition can be carried out at 300 to 900°C. Under these conditions, silicon precursor gas can be easily deposited inside the pores of the calcined product, allowing nanosilicon to be easily filled.

[0210] (S60) Step of forming the first coating layer

[0211] The above step is to manufacture a composite in which a first coating layer is formed on the outer surface of the sintered product by heat-treating the sintered product using a hard coating material.

[0212] In one embodiment, the first coating layer may be formed by including the step of heat-treating the sintered product at 500 to 1200°C using a hard coating material. When heat-treated at the above temperature, a composite including the first coating layer can be easily formed. For example, heat treatment may be performed at 600 to 1200°C or 850 to 1100°C.

[0213] For example, the hard coating material may include a carbon-based material having a pencil hardness of 4H to 7H. For example, the NanoMollisAdamas product from Lemon Energy can be used as the hard coating material.

[0214] The hard coating material may be amorphous. In addition, the hard coating material is formed by self-assembly, has excellent isotropic properties, and has excellent thermal stability, so no structural change occurs even at high temperatures (approx. 3000℃).

[0215] In one embodiment, the hard coating material may have an electrical resistance of 3 to 5 μΩ·m. Under the above conditions, the electrical conductivity of the cathode material may be excellent.

[0216] In one embodiment, the hard coating material may have an average particle size of 50 nm to 1 µm. Workability may be excellent under the above conditions. For example, the hard coating material may have an average particle size of 5 to 500 nm, 10 to 500 nm, 50 to 500 nm, or 50 to 200 nm.

[0217] The hard coating material may have high gas impermeability and excellent chemical resistance and electrical conductivity. In addition, the hard coating material may be dust-free and have a purity (impurity content) of 5 ppm or less or 2 ppm or less. Under these conditions, the strength and electrical properties may be excellent, and the electrical conductivity of the cathode material may be excellent.

[0218] In one embodiment, the hard coating material and the solvent may be applied in the form of a hard coating liquid. In one embodiment, the solvent may include one or more of water, an ethanol-based solvent, an amide-based solvent, an ester-based solvent, and a hydrocarbon-based solvent. When the solvent is included, the mixability and workability may be excellent. The alcohol-based solvent may include one or more of methanol, ethanol, isopropanol, and butanol. The amide-based solvent may include one or more of N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAC), and dimethylformamide (DMF). The hydrocarbon-based solvent may include one or more of toluene and xylene.

[0219] In one embodiment, the heat treatment may be carried out in an inert gas atmosphere. The inert gas may include one or more of nitrogen and argon.

[0220] Referring to FIG. 2 above, the first coating layer (30) can be formed by penetrating at least a portion of the pores (12) of the sintered material (or carbon carrier (10)). For example, the first coating layer can be formed by penetrating the outer surface of the carbon carrier and the space inside the carbon carrier pores that are not filled with the nanosilicon. Under these conditions, cracking or damage to the cathode material due to the expansion of the nanosilicon can be prevented.

[0221] In one embodiment, the first coating layer may be formed by penetrating into the pores formed on the surface of the carbon carrier to a depth of 0.05 μm or more. Referring to FIG. 2, the penetration depth of the first coating layer may refer to a distance measured in the vertical direction relative to the surface of the carbon carrier. When the first coating layer is formed by penetrating into the pores on the surface of the carbon carrier as described above, it prevents cracking or damage to the cathode material caused by the expansion of the nanosilicon, and may exhibit excellent electrical conductivity and long life characteristics. For example, the first coating layer may be formed by penetrating into the pores on the surface of the carbon carrier to a depth of 0.1 to 2 μm or 0.3 to 1.5 μm.

[0222] In one sphere, the first coating layer may have a pencil hardness of 4H or higher as measured according to ISO 15184. Under these conditions, volume changes due to the expansion and contraction of nanosilicon during charging and discharging of the cathode material can be easily controlled, and high power output and long life characteristics may be excellent. For example, the first coating layer may have a pencil hardness of 4.5H to 7H or 5H to 7H as measured according to ISO 15184.

[0223] For example, the first coating layer may have a higher pencil hardness than the carbon carrier. Under the above conditions, volume changes due to the expansion and contraction of nanosilicon during charging and discharging of the cathode material can be easily controlled, and high power output and long lifespan characteristics may be excellent.

[0225] (S70) Second coating layer formation step

[0226] The above step is to heat-treat a first mixture containing the composite and graphene to form a second coating layer on the outer surface of the composite.

[0227] In one embodiment, the first mixture may comprise 100 parts by weight of the composite and 0.1 to 30 parts by weight of graphene. Under these conditions, a second coating layer can be easily formed. For example, the graphene may be included in 0.1 to 20 parts by weight, 1 to 20 parts by weight, 1 to 15 parts by weight, 1 to 10 parts by weight, or 1 to 8 parts by weight.

[0228] In one embodiment, the graphene may have an average size of 10 to 5000 nm. The size may refer to the maximum length or diameter (particle size) of the graphene. For example, the graphene may be spherical. For example, the graphene may be 50 to 5000 nm, 100 to 5000 nm, 300 to 5000 nm, 500 to 5000 nm, or 500 to 1000 nm.

[0229] In one embodiment, the graphene may be formed by milling graphite powder. For example, the graphene may be formed by including the step of milling the graphite powder.

[0230] The graphene can be formed by including a step of separating the graphite layers while simultaneously refining the graphite particles through a milling process using one or more of natural graphite and artificial graphite. The milling can be performed, for example, for 20 to 80 minutes or 30 to 70 minutes. Under these conditions, graphene can be easily formed from the graphite powder.

[0231] In one embodiment, the graphene may comprise a layer structure of 1 to 10 layers. Under the above conditions, the electrical conductivity and capacitance characteristics of the cathode material may be excellent, and high power and long life characteristics may be excellent. For example, the graphene may comprise a layer structure of 2 to 8 layers or 2 to 5 layers.

[0232] In one embodiment, the first mixture may further include a solvent and a dispersant.

[0233] In one embodiment, the solvent may include one or more of water, ethanol, isopropyl alcohol, and potassium hydroxide (KOH). When the solvent is included, the graphite raw material powder is not oxidized, and the mixability and dispersibility of the first mixture may be excellent.

[0234] In one embodiment, the dispersant may include one or more of polyvinylpyrrolidone, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, stearic acid, palmitic acid, oleic acid, and lauric acid. As another example, the dispersant may include one or more of stearic acid, petroleum pitch, coal pitch, coal tar, glucose, sucrose, polyimide, polyacrylic acid (PAA), and polyvinyl alcohol (PVA). When the dispersant is included, the dispersibility of the graphite powder is excellent, so the first mixture can be easily prepared. For example, it may include stearic acid. For example, the dispersant may be used by mixing stearic acid and N-methylpyrrolidone (NMP).

[0235] In one embodiment, the first mixture may comprise 100 parts by weight of a composite, 0.1 to 30 parts by weight of graphene, 5 to 1500 parts by weight of a solvent, and 0.1 to 30 parts by weight of a dispersant. Under these conditions, the mixability and dispersibility of the components of the first mixture are excellent, and the first mixture in the form of a slurry can be easily prepared.

[0236] For example, a dispersant may be added to the solvent in the aforementioned amount and mixed, then the composite and graphene may be added and mixed to produce a dispersion, and the dispersion may be ground to produce a first mixture in the form of a slurry.

[0237] In one embodiment, the first mixture can be heat-treated at 600 to 1100°C to form the second coating layer. Under these heat treatment conditions, the second coating layer can be easily formed. When heat-treated under these conditions, the second coating layer is easily formed on the outer surface of the composite of the first mixture, and the phenomenon in which the resistance value increases due to the second coating layer being formed thicker than necessary on the outer surface of the composite is prevented, thereby preventing a decrease in the mobility of lithium ions or a reduction in the lithium storage space of the graphite. In addition, it can be economically efficient by preventing an increase in carbon precursor gas consumption and energy consumption.

[0238] The heat treatment of the first mixture above may be carried out under inert gas conditions. For example, the inert gas may include one or more of nitrogen and argon.

[0239] In one embodiment, the cathode material may include the second coating layer and the first coating layer in a weight ratio of 1:0.5 to 1:6. Under these conditions, the durability and structural stability of the cathode material are excellent, preventing damage to the cathode material during charging and discharging, and may exhibit excellent long life characteristics, high power output, and electrical characteristics. For example, the cathode material may include the second coating layer and the first coating layer in a weight ratio of 1:1 to 1:6, 1:1.5 to 1:5, or 1:2 to 1:4.

[0241] lithium secondary battery containing a negative electrode material

[0242] Another aspect of the present invention relates to a lithium secondary battery comprising the above-mentioned cathode material (or carbon carrier). In one embodiment, the lithium secondary battery comprises a positive electrode; a negative electrode; and an electrolyte formed between the positive electrode and the negative electrode, wherein the negative electrode comprises the above-mentioned cathode material (or carbon carrier).

[0243] In one embodiment, the lithium secondary battery may include: a positive electrode comprising a positive electrode material; a negative electrode spaced apart from the positive electrode and comprising a negative electrode material; an electrolyte disposed between the negative electrode and the positive electrode; and a separator disposed between the negative electrode and the positive electrode to prevent an electrical short circuit between the negative electrode and the positive electrode.

[0244] In one embodiment, the anode and cathode may each be manufactured by applying a mixture containing an anode material (or cathode material), a conductive material, and a binder to one surface of an electrode plate (current collector), and then drying and pressing.

[0245] In one embodiment, the positive electrode plate and the negative electrode plate may each include one or more of copper, stainless steel, aluminum, nickel, and titanium.

[0246] In one embodiment, the cathode material may comprise a composite oxide of a metal and lithium. The metal may comprise one or more of cobalt (Co), manganese (Mn), aluminum (Al), and nickel (Ni). For example, it may comprise one or more of lithium-nickel oxide, lithium-nickel-cobalt oxide, lithium-nickel-cobalt-manganese oxide, and lithium-nickel-cobalt-aluminum oxide.

[0247] In one embodiment, the conductive material may include one or more of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, carbon fiber, metal fiber, fluorinated carbon, aluminum, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene-based compounds.

[0248] In one embodiment, the binder may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), styrene-based rubber, and fluorine-based rubber.

[0249] In one embodiment, the separator may be a conventional one. For example, the separator may include one or more of polyester, polyethylene, polypropylene, and polytetrafluoroethylene (PTFE). The separator may be in the form of a nonwoven fabric or a woven fabric. The separator is porous with an average pore diameter of 0.01 to 10 μm, and the separator may have a thickness of 5 to 500 μm.

[0250] In one embodiment, the electrolyte may include a non-aqueous organic solvent and a lithium salt. For example, the non-aqueous organic solvent may include one or more of carbonate-based, ester-based, ether-based, and ketone-based solvents. The carbonate-based solvent may include one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylmethyl carbonate (EMC), ethylpropyl carbonate (EPC), ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC).

[0251] The above ester-based solvent may include one or more of butyrolactone, decanolide, valerolactone, caprolactone, n-methyl acetate, n-ethyl acetate, and n-propyl acetate. The above ether-based solvent may include dibutyl ether, etc. The above ketone-based solvent may include polymethylvinyl ketone.

[0252] The above lithium salt can serve as a source of lithium ions within the battery. For example, the lithium salt may include, but is not limited to, one or more of LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiAlO4, and LiAlCl4.

[0253] In one embodiment, the electrolyte may further include one or more of vinylene carbonate, vinyl ethylene carbonate, monofluoroethylene carbonate, difluoroethylene carbonate, succinic anhydride, and 1,3-propane sultone.

[0254] In one embodiment, the lithium secondary battery may include a prismatic battery, a cylindrical battery, and a pouch-type battery.

[0256] Hereinafter, the structure and operation of the present invention will be explained in more detail through preferred embodiments. However, these are presented as preferred examples of the present invention and should not be interpreted in any way as limiting the present invention. Details not described herein can be sufficiently technically inferred by those skilled in the art, so such descriptions will be omitted.

[0258] Examples and Comparative Examples

[0259] Example 1

[0260] (1) Preparation of carbon carrier: A carbon precursor was prepared containing an inorganic polymer (polysiloxane) and an organic polymer (phenol resin) in a weight ratio of 1:3. Then, a carbon precursor mixture was prepared containing 75 wt% of the carbon precursor, 20 wt% of a crosslinking agent (triethanolamine), and 5 wt% of a dispersion solvent (N-methyl-2-pyrrolidone (NMP)). The carbon precursor mixture was heated to 110 to 200°C and then cooled to -40°C to prepare an intermediate. Then, the intermediate was ground to prepare a ground product.

[0261] The above-mentioned pulverized material was subjected to activation heat treatment at 650–1150°C for 1–10 hours under carbon dioxide conditions, and then the pulverized material subjected to activation heat treatment was calcined at 900–1100°C under inert gas (nitrogen) conditions to produce a calcined material. Then, the calcined material was classified to produce a carbon carrier.

[0262] (2) Chemical vapor deposition: A sintered product was prepared by chemically vapor infiltration (CVI) a silicon precursor gas (dichlorosilane gas) into the pores of the carbon carrier.

[0263] (3) Formation of the first coating layer and preparation of the composite: As a hard coating material, a carbon-based material (NanoMollisAdamas from Lemon Energy) with an average particle size (d50) of 0.05 to 0.5 μm and a pencil hardness of 4 to 6 H according to ISO 15184 standards was prepared.

[0264] A mixture comprising the chemically vapor-deposited sintered product and the hard coating material was heat-treated at 900 to 1050°C in an inert gas atmosphere to form a first coating layer on the outer surface of the sintered product, thereby manufacturing a composite.

[0265] (4) Formation of the second coating layer: Spherical artificial graphite powder was mechanically milled using zirconia balls at 50 to 100 rpm for 60 minutes (KM Tech Co., Gyro mixer milling machine) to remove rough parts of the graphite and produce graphene having a 2 to 5 layer structure. Then, 100 parts by weight of the composite, 1 to 10 parts by weight of the produced graphene, 100 to 250 parts by weight of a dispersion solvent, and 1 to 5 parts by weight of a dispersant were mixed in a known method to produce the first mixture.

[0266] Then, the first mixture was heat-treated at 700 to 1000°C in a nitrogen gas atmosphere to form a second coating layer on the outer surface of the composite to produce a cathode material.

[0267] The above cathode material comprises 40-60 wt% carbon carrier, 20-40 wt% nanosilicon, 10-15 wt% first coating layer, and 5-10 wt% second coating layer, and the second coating layer and the first coating layer are included in a weight ratio of 1:2 to 1:3.

[0268] The above-described cathode material comprises a porous carbon carrier, nanosilicon filled in the pores of the carbon carrier, a first coating layer formed on the outer surface of the carbon carrier, and a second coating layer formed on the outer surface of the first coating layer. The porous carbon carrier includes tunnel-shaped pores branched from the inside toward the surface, wherein the tunnel-shaped pores are connected to each other to form a continuous network. The first coating layer is formed by penetrating into the pores formed on the surface of the carbon carrier to a depth of 0.3 to 1.2 μm.

[0269] The penetration depth of the first coating layer of the above example was measured using a field emission scanning electron microscope (FESEM, BRUKER, product name: Xflash) to measure the pore penetration depth of the first coating layer in a vertical direction relative to the surface of the carbon carrier.

[0270] The carbon carrier has a pencil hardness of 4H according to ISO 15184 standards, the first coating layer has a pencil hardness of 6H according to ISO 15184 standards, and the second coating layer has a pencil hardness of 1H according to ISO 15184 standards.

[0272] Example 2

[0273] A carbon precursor was prepared comprising an inorganic polymer (polysiloxane) and an organic polymer (including a 1:2 weight ratio of phenol resin and polystyrene) in a 1:3 weight ratio. Then, a carbon precursor mixture was prepared comprising 70 wt% of the carbon precursor, 25 wt% of a crosslinking agent (triethanolamine), and 5 wt% of a dispersion solvent (N-methyl-2-pyrrolidone (NMP)). A cathode material was prepared in the same manner as in Example 1, except that the carbon precursor mixture was heated to 110–200°C and then cooled to -40°C to produce an intermediate.

[0274] The above cathode material comprises 40-60 wt% carbon carrier, 20-40 wt% nanosilicon, 10-15 wt% first coating layer, and 5-10 wt% second coating layer, and the second coating layer and the first coating layer are included in a weight ratio of 1:2 to 1:3.

[0275] The above-described cathode material comprises a porous carbon carrier, nanosilicon filled in the pores of the carbon carrier, a first coating layer formed on the outer surface of the carbon carrier, and a second coating layer formed on the outer surface of the first coating layer. The porous carbon carrier includes tunnel-shaped pores branched from the inside toward the surface, wherein the tunnel-shaped pores are connected to each other to form a continuous network. The first coating layer is formed by penetrating into the pores formed on the surface of the carbon carrier to a depth of 0.4 to 1.1 μm.

[0276] The carbon carrier has a pencil hardness of 4.5H according to ISO 15184 standards, the first coating layer has a pencil hardness of 6H according to ISO 15184 standards, and the second coating layer has a pencil hardness of 1H according to ISO 15184 standards.

[0278] Example 3

[0279] (1) Carbon carrier manufacturing: A cathode material was manufactured in the same manner as in Example 1, except that the pulverized material that was activated heat-treated in Example 1 was first calcined by heating and maintaining it at 900 to 1100°C under an inert gas (nitrogen) condition at a pressure of 3 to 7 atm, and the pulverized material that was first calcined was second calcined at 1100 to 1700°C under an inert gas (nitrogen) condition at a pressure of 0.5 to 0.8 atm.

[0280] The above cathode material comprises 40-60 wt% carbon carrier, 20-40 wt% nanosilicon, 10-20 wt% first coating layer, and 4-10 wt% second coating layer, and the second coating layer and the first coating layer are included in a weight ratio of 1:2.5 to 1:5.

[0281] The above-described cathode material comprises a porous carbon carrier, nanosilicon filled in the pores of the carbon carrier, a first coating layer formed on the outer surface of the carbon carrier, and a second coating layer formed on the outer surface of the first coating layer. The porous carbon carrier includes tunnel-shaped pores branched from the inside toward the surface, wherein the tunnel-shaped pores are connected to each other to form a continuous network. The first coating layer is formed by penetrating into the pores formed on the surface of the carbon carrier to a depth of 0.3 to 1.3 μm.

[0282] The carbon carrier has a pencil hardness of 4.5H according to ISO 15184 standards, the first coating layer has a pencil hardness of 7H according to ISO 15184 standards, and the second coating layer has a pencil hardness of 1H according to ISO 15184 standards.

[0284] Example 4

[0285] (1) Carbon carrier manufacturing: A cathode material was manufactured in the same manner as in Example 1, except that the pulverized material that was activated heat-treated in Example 2 was first calcined by heating and maintaining it at 900 to 1100°C under an inert gas (nitrogen) condition at a pressure of 3 to 7 atm, and the pulverized material that was first calcined was second calcined at 1100 to 1700°C under an inert gas (nitrogen) condition at a pressure of 0.5 to 0.8 atm.

[0286] The above cathode material comprises 40-60 wt% carbon carrier, 20-40 wt% nanosilicon, 10-15 wt% first coating layer, and 5-10 wt% second coating layer, and the second coating layer and the first coating layer are included in a weight ratio of 1:2 to 1:3.

[0287] The above-described cathode material comprises a porous carbon carrier, nanosilicon filled in the pores of the carbon carrier, a first coating layer formed on the outer surface of the carbon carrier, and a second coating layer formed on the outer surface of the first coating layer. The porous carbon carrier includes tunnel-shaped pores branched from the inside toward the surface, wherein the tunnel-shaped pores are connected to each other to form a continuous network. The first coating layer is formed by penetrating into the pores formed on the surface of the carbon carrier to a depth of 0.3 to 1.2 μm.

[0288] The carbon carrier has a pencil hardness of 4.5H according to ISO 15184 standards, the first coating layer has a pencil hardness of 7H according to ISO 15184 standards, and the second coating layer has a pencil hardness of 2H according to ISO 15184 standards.

[0290] Example 5

[0291] A carbon precursor comprising an organic polymer (hydrogenated nitrile butadiene rubber (H-NBR)) was prepared. Then, a cathode material was prepared in the same manner as in Example 1, except that a carbon precursor mixture comprising 80 wt% of the carbon precursor, 15 wt% of a crosslinking agent (triethanolamine), and 5 wt% of a dispersion solvent (N-methyl-2-pyrrolidone (NMP)) was applied.

[0292] The above-described cathode material comprises a porous carbon carrier, nanosilicon filled in the pores of the carbon carrier, a first coating layer formed on the outer surface of the carbon carrier, and a second coating layer formed on the outer surface of the first coating layer. The porous carbon carrier includes tunnel-shaped pores branched from the inside toward the surface, wherein the tunnel-shaped pores are connected to each other to form a continuous network. The first coating layer is formed by penetrating into the pores formed on the surface of the carbon carrier to a depth of 0.3 to 0.9 μm.

[0293] The carbon carrier has a pencil hardness of 4.5H according to ISO 15184 standards, the first coating layer has a pencil hardness of 6H according to ISO 15184 standards, and the second coating layer has a pencil hardness of 1H according to ISO 15184 standards.

[0295] Example 6

[0296] A carbon precursor comprising an inorganic polymer (polysiloxane) was prepared. Then, a cathode material was prepared in the same manner as in Example 1, except that a carbon precursor mixture comprising 80 wt% of the carbon precursor, 15 wt% of a crosslinking agent (triethanolamine), and 5 wt% of a dispersion solvent (N-methyl-2-pyrrolidone (NMP)) was applied.

[0297] The above-described cathode material comprises a porous carbon carrier, nanosilicon filled in the pores of the carbon carrier, a first coating layer formed on the outer surface of the carbon carrier, and a second coating layer formed on the outer surface of the first coating layer. The porous carbon carrier includes tunnel-shaped pores branched from the inside toward the surface, wherein the tunnel-shaped pores are connected to each other to form a continuous network. The first coating layer is formed by penetrating into the pores formed on the surface of the carbon carrier to a depth of 0.4 to 1.3 μm.

[0298] The carbon carrier has a pencil hardness of 4H according to ISO 15184 standards, the first coating layer has a pencil hardness of 6H according to ISO 15184 standards, and the second coating layer has a pencil hardness of 1H according to ISO 15184 standards.

[0300] Comparative Example 1

[0301] A cathode material was prepared in the same manner as in Example 1, except that a calcined product prepared by calcining the activated pulverized material from Example 1 at 860°C under inert gas (nitrogen) conditions was applied.

[0303] Comparative Example 2

[0304] A sintered product was prepared by calcining the pulverized product activated in Example 1 at 780°C under inert gas (nitrogen) conditions, and a cathode material was prepared in the same manner as in Example 1, except that a second coating layer was not formed.

[0306] Experimental Example

[0307] (1) Raman spectrum analysis of the cathode material: The cathode materials of the above examples and comparative examples were analyzed by Raman Spectroscopy, and the results are shown in Table 1 below. The Raman analysis was performed using a 532 nm green laser (manufactured by Nanoscope Systems, product name: NS240) and a 785 nm NIR laser (manufactured by HORIBA, product name: LabRAM Evolution) as excitation sources.

[0309] (2) X-ray diffraction analysis of carbon carriers: X-ray diffraction analysis was performed on the above examples and comparative examples.

[0310] First, the sintered products (carbon carriers) of the examples and comparative examples were analyzed by measuring them using X-ray diffraction (XRD) spectra with CuKα rays of 1.54 Å wavelength using a measuring instrument (Malvern Panalytical, Empyrean).

[0311] The above X-ray diffraction analysis was performed using an analyzer (Malvern Panalytical, Empyrean) with CuKα rays of 1.54178 Å, measuring 2θ as 10-70° with a step size of 0.01°, and the full width at half maximum (FWHM) of the X-ray diffraction angle (2θ) using CuKα rays of the carbon carrier (002) plane was calculated and the results are shown in Table 1 below.

[0313] (3) X-ray diffraction analysis of nanosilicon: For the nanosilicon of the example and comparative example, the diffraction angle (2θ) values ​​of the (111) and (220) planes were measured to determine the full width at half maximum (FWHM) values, and Equation 1 (IS(111) / IS(220)) was calculated and shown in Table 1 below. Specifically, the diffraction angle (2θ) values ​​of the (111) and (220) planes of the nanosilicon particles were determined by measuring the nanosilicon particles in the negative electrode active materials of the example and comparative example using X-ray diffraction (XRD) spectra with CuKα rays of wavelength 1.54 Å using a measuring instrument (Malvern Panalytical, Empyrean) to derive the full width at half maximum values.

[0315] (4) Tap density (g / cm²) 3 ) and pencil hardness: The tap density of the cathode materials of the above examples and comparative examples, and the pencil hardness of the first coating layer and the second coating layer were measured respectively in accordance with ISO 15184 standards, and the results are shown in Table 1 below.

[0316]

[0317] Referring to the results in Table 1 above, the carbon carriers of Examples 1 to 6 have a D-band of 1,250 to 1,350 cm⁻¹ in the Raman spectrum. -1 Wavenumber range and G-band are 1,550 to 1,650 cm -1 Each has a peak value in the wavenumber range, and the D-band peak intensity (I) relative to the G-band peak intensity. D / I G It was found that ) satisfies 1.3 or less.

[0318] In addition, it was found that the nanosilicons of Examples 1 to 6 each satisfied a full width at half maximum (FWHM) of the X-ray diffraction angle (2θ) using CuKα lines of the (111) and (220) planes of 0.4° to 0.8°. Furthermore, it was found that all of the nanosilicons of Examples 1 to 6 each had an effective peak in the region where the diffraction angle (2θ) value in the (111) plane was 26 to 30° and the diffraction angle (2θ) value in the (220) plane was 47 to 50° in the X-ray diffraction spectrum, and satisfied the value of Equation 1 of 1.2 to 1.8, thereby securing high capacity and high power characteristics of the nanosilicon and having an excellent effect of preventing breakage of silicon particles during charging and discharging.

[0319] In addition, Examples 1 to 6 satisfied the carbon carrier XRD (002) plane FWHM of 3 to 10° and the XRD (002) plane FWHM of the first coating layer of 3 to 6°, and the second coating layer of Examples 1 to 6 satisfied the 2D-band peak intensity (I) for the 1G-band peak intensity measured at a 532 nm laser 2D / I 1G It was found that the durability and electrical conductivity of the second coating layer were excellent, and the high capacity and high power characteristics of the cathode active material were secured.

[0320] On the other hand, Comparative Example 1 is (I D / I G It was found that when a negative electrode material is manufactured by filling the pores with silicon, the durability is reduced compared to Examples 1 to 6 because the value is greater than 1.3, and the effect of buffering silicon volume expansion and contraction during charging and discharging is reduced.

[0322] (5) Pore analysis and specific surface area (BET method) measurement: The gas (nitrogen) pores of the cathode materials of the above examples and comparative examples were measured using Microtrac’s BELSORP MAX X product, and the total pore volume (cm²) 3 / g) was measured.

[0323] In addition, the volume percentage of micro pores with a diameter greater than 0 and less than 2 nm, meso pores with a diameter greater than 2 nm and less than 50 nm, and macro pores with a diameter greater than 50 nm and less than 200 nm in the above cathode material was measured, and the results are shown in Table 2 below.

[0324] In addition, the specific surface area (BET) of the cathode material for the above examples and comparative examples was measured, and the results are shown in Table 2 below.

[0326] (6) Gas permeability measurement: For the cathode materials of the above examples and comparative examples, gas permeability (cc / m²) was measured using a measuring instrument (GBPI N500L) in accordance with ASTM D 1434 standards under pressure conditions of 0.1 to 1 kPa. 2 ·day) was measured and the results are shown in Table 2 below.

[0327]

[0328] Referring to the results of Table 2 above, the pore analysis results showed that Examples 1 to 6 had lower total pore volume and specific surface area compared to Comparative Examples 1 and 2, and had lower gas permeability. Through this, it was found that the cathode materials of the examples have superior carbon carrier durability and lower gas permeability compared to the comparative examples, and can easily control volume changes due to the expansion and contraction of silicon during charging and discharging of the cathode material, and have excellent output characteristics.

[0330] (7) Particle size analysis: The particle size of the cathode materials (carbon carriers) of the above examples and comparative examples was analyzed using an analysis instrument (manufactured by Anton Paar, product name: PSA 1090L / D). Specifically, the D10, D50, and D90 values ​​of the cathode materials and the span value of (D90-D10) / D50 were measured, and the results are shown in Table 3 below.

[0332] (8) Oxygen permeability measurement: Oxygen permeability was measured for the first coating layers of Examples 1 to 6 and Comparative Examples 1 to 2, and the results are shown in Table 3 below. The oxygen permeability was measured according to ASTM D3985 standards using a measuring instrument (OX-TRAN 2 / 21MD, manufactured by MOCON).

[0333] Specifically, a first coating layer with a thickness of 150 nm was formed on the surface of a carbon carrier (fired product) in the same manner as in Example 1 above to prepare circular samples (diameter 50 mm, thickness 1 mm or less). The oxygen permeability measurement results for the samples are shown in Table 3 below.

[0334]

[0335] Referring to the results of Table 3 above, it was found that Examples 1 to 6 have excellent uniformity of particle size distribution compared to Comparative Examples 1 to 2, and thus possess uniform electrochemical characteristics. Additionally, Examples 1 to 6 have low oxygen permeability, which allows for easy control of volume changes due to the expansion and contraction of silicon during charging and discharging of the cathode material, and thus can have excellent output characteristics.

[0337] Experimental Example (2)

[0338] (1) Manufacture of cathode material and secondary battery: A pouch-type full cell was manufactured using the cathode materials of the above examples and comparative examples. Specifically, a cathode slurry having a capacity of about 364 mAh / g was prepared by mixing 97.1 wt% of a mixed cathode material containing graphite with the cathode materials of the above examples and comparative examples, 1.65 wt% of CMC (carboxymethyl cellulose), and 1.25 wt% of styrene-butadiene rubber (SBR). The above mixed cathode material was applied by mixing the cathode material and graphite in a weight ratio of 1:9, 2:8, and 3:7.

[0339] Subsequently, the slurries prepared in the above examples and comparative examples were coated and dried onto a current collector for the cathode, and then rolled to produce the respective cathodes. The loading amount of the cathode was 6.5±0.5 mg / cm² 2 It was, and the electrode density was 1.55~1.60 g / cc.

[0340] Next, a pouch cell with a capacity of 1.0 Ah was manufactured using a conventional method by using an anode (NCM811) as the counter electrode to the above-manufactured cathode, and using an electrolyte and a separator (including polypropylene and polyethylene).

[0341] At this time, the above electrolyte was prepared by dissolving 1M LiPF6 in a mixed solvent of ethylmethyl carbonate (EMC) and ethylene carbonate (EC) (EMC and EC = 5:5 volume ratio) and used.

[0343] (2-1) Electrochemical evaluation (1): For the full cells of the above examples and comparative examples, the resistance of the electrode and electrolyte interface was measured after initial operation and 500 cycles of operation. The resistance was measured using electrochemical impedance spectroscopy (EIS), which analyzes the resistance component (impedance) inside the battery by frequency by applying a small AC signal to the full cell and measuring the response. The results were measured in the frequency range from 1000 kHz to 0.1 Hz using ZIVE SP1 (manufactured by WonAtech) and are shown in Table 4 below. In addition, the shape of the Nyquist plot for the full cells of the examples and comparative examples (mixed cathode materials with cathode material and graphite applied in weight ratios of 1:9, 2:8, and 3:7) measured by EIS is shown in Figure 3.

[0344]

[0346] In Table 4 above, the mixed cathode material (1) is a mixed cathode material in which the cathode material and graphite are applied in a weight ratio of 1:9, the mixed cathode material (2) is a mixed cathode material in which the cathode material and graphite are applied in a weight ratio of 2:8, and the mixed cathode material (3) is a mixed cathode material in which the cathode material and graphite are applied in a weight ratio of 3:7.

[0347] Figure 3(a) is a Nyquist plot for the resistance value during EIS analysis before operation (0 cycles) of the secondary batteries of the example and comparative example (using a mixed negative electrode material with a negative electrode material and graphite in a 1:9 weight ratio), and Figure 3(b) is a Nyquist plot for the resistance value during EIS analysis after 500 cycles of operation of the secondary batteries of the example and comparative example (using a mixed negative electrode material with a negative electrode material and graphite in a 1:9 weight ratio).

[0348] Referring to Table 4 and Figure 3 above, it was found that Examples 1 to 6 had lower ion transfer resistance than Comparative Examples 1 to 2.

[0350] (2-2) Electrochemical evaluation (2): After aging the full cell of the above example and comparative example at room temperature (25℃) for more than 20 hours, an electrochemical evaluation (charge / discharge test) was performed at room temperature.

[0351] Specifically, for the full cells of the examples and comparative examples, the cut-off voltage was set to 0.01V (0.01C), and after charging in CC-CV mode at a rate of 0.2C, the cells were discharged in CC mode to 1.5V at a rate of 0.2C, and up to 500 charge-discharge cycles were performed. The lifespan (capacity retention rate) characteristics of the examples and comparative examples after 500 charge-discharge cycles are shown in Figures 4 to 6 and Table 5 below.

[0352]

[0354] In Table 5 above, the mixed cathode material (1) is a mixed cathode material in which the cathode material and graphite are applied in a weight ratio of 1:9, the mixed cathode material (2) is a mixed cathode material in which the cathode material and graphite are applied in a weight ratio of 2:8, and the mixed cathode material (3) is a mixed cathode material in which the cathode material and graphite are applied in a weight ratio of 3:7.

[0355] Figure 4 is a graph showing the change in specific capacity according to the operation of the example and comparative example secondary batteries (applying a mixed negative electrode material with a negative electrode material and graphite in a weight ratio of 1:9), Figure 5 is a graph showing the change in specific capacity according to the operation of the example and comparative example secondary batteries (applying a mixed negative electrode material with a negative electrode material and graphite in a weight ratio of 2:8), and Figure 6 is a graph showing the change in specific capacity according to the operation of the example and comparative example secondary batteries (applying a mixed negative electrode material with a negative electrode material and graphite in a weight ratio of 3:7).

[0356] Referring to the results of Figures 4 to 6 and Table 5 above, it was found that Examples 1 to 6 had an excellent buffering effect on the expansion and contraction of silicon during charging and discharging of the secondary battery compared to Comparative Examples 1 and 2, and as a result of EIS measurement, the resistance was reduced and the ion transfer rate was excellent, and the capacity retention rate, charge / discharge efficiency, and long-term life characteristics were excellent.

[0358] The present invention has been described above with reference to embodiments. Those skilled in the art will understand that the present invention may be embodied in modified forms without departing from the essential characteristics of the invention. Therefore, the disclosed embodiments should be considered in an illustrative rather than a restrictive sense. The scope of the invention is defined by the claims, not by the foregoing description, and all variations within the scope of equivalents should be interpreted as being included in the invention.

Claims

Claim 1 A cathode material comprising: a porous carbon carrier; nanosilicon filled in the pores of the carbon carrier; a first coating layer formed on the outer surface of the carbon carrier; and a second coating layer formed on the outer surface of the first coating layer and having a lower hardness than the first coating layer; wherein the carbon carrier has a higher hardness than the second coating layer, and the first coating layer is formed by penetrating at least a portion of it into the pores of the carbon carrier, and the cathode material has a D-band peak intensity (I) relative to the G-band peak intensity in a Raman spectrum D / I G A negative electrode material for a lithium secondary battery having ) 1.3 or less. Claim 2 In claim 1, the carbon carrier has a pencil hardness of 1H to 6H and a skeletal density of 0.3 g / cm³ as measured in accordance with ISO 15184. 3 That is all, and the above-mentioned first coating layer has a pencil hardness of 4H or higher and a density of 1.0 g / cm³ as measured in accordance with ISO 15184. 3 It exceeds, and the above-mentioned second coating layer has a pencil hardness of B to 3H and a density of 1.0 g / cm³ as measured in accordance with ISO 15184. 3 A negative electrode material for lithium secondary batteries. Claim 3 In claim 1, the negative electrode material comprises 20 to 70 weight% of a carbon carrier, 10 to 70 weight% of nanosilicon, 1 to 30 weight% of a first coating layer, and 1 to 20 weight% of a second coating layer, for use as a negative electrode material for a lithium secondary battery. Claim 4 A negative electrode material for a lithium secondary battery according to claim 1, wherein the nanosilicon has an average particle size of 0.5 to 100 nm and has effective peaks in the regions where the diffraction angle (2θ) value in the (111) plane is 26 to 30˚ and the diffraction angle (2θ) value in the (220) plane is 47 to 50˚, respectively. Claim 5 In claim 1, the nanosilicon is a negative electrode material for a lithium secondary battery, wherein the X-ray diffraction peak using CuKα rays satisfies the following Equation 1: [Equation 1]3 ≤ IS(111) / IS(220) ≤ 10 (wherein Equation 1, IS(111) is the maximum peak intensity at the (111) plane of the nanosilicon, and IS(220) is the maximum peak intensity at the (220) plane of the nanosilicon). Claim 6 A negative electrode material for a lithium secondary battery according to claim 1, wherein the carbon carrier comprises tunnel-shaped pores branched from the interior toward the surface, and the tunnel-shaped pores are connected to each other to form a continuous network. Claim 7 In claim 6, the carbon carrier comprises, with respect to the total pore volume, 60 to 99 volume% of micro pores with a diameter of 2 nm or less and 1 to 40 volume% of meso pores with a diameter greater than 2 nm and less than or equal to 50 nm. It is a negative electrode material for a lithium secondary battery. Claim 8 delete Claim 9 A negative electrode material for a lithium secondary battery according to claim 1, wherein the first coating layer is formed by penetrating into the pores formed on the surface of the carbon carrier to a depth of 0.05 μm or more. Claim 10 A negative electrode material for a lithium secondary battery according to claim 1, wherein the carbon carrier has a full width at half maximum (FWHM) of an X-ray diffraction angle (2θ) using CuKα rays of the (002) plane of 3˚ to 10˚, and the first coating layer has a full width at half maximum (FWHM) of an X-ray diffraction angle (2θ) using CuKα rays of the (002) plane of 3˚ to 6˚. Claim 11 In claim 1, the first coating layer has an oxygen permeability of 4.0 x 10 -7 Up to 4.0 X 10 -2 darcy phosphorus, negative electrode material for lithium secondary batteries. Claim 12 In claim 1, the second coating layer is the 2D-band peak intensity (I) relative to the G-band peak intensity in the Raman spectrum 2D / I G A negative electrode material for a lithium secondary battery having a value of 0.35 to 0.

85. Claim 13 In claim 1, the carbon carrier is a negative electrode material for a lithium secondary battery in which the X-ray diffraction peak using CuKα rays satisfies the following Equation 2: [Equation 2] 5 ≤ I(002) / I(100) ≤ 20 (wherein Equation 2, I(002) is the maximum peak intensity on the (002) plane of the carbon carrier, and I(100) is the maximum peak intensity on the (100) plane of the carbon carrier). Claim 14 In claim 1, the carbon carrier has a total pore volume of 0.3 to 1.0 cm² 3 / g, porosity 10–90%, tap density 0.7 g / cm³ 3 Ideal and specific surface area (BET) 1,400–1,800 m² 2 / g, and the above cathode material has a total pore volume of 0.01 cm³ 3 / g or less, tap density 0.8 g / cm³ 3 Ideal and specific surface area (BET) 5m² 2 A negative electrode material for lithium secondary batteries with a content of / g or less. Claim 15 In claim 1, the cathode material has an average particle size of 0.5 to 5 μm and a span value of (D90-D10) / D50 of 2.0 or less, for use as a cathode material for a lithium secondary battery. Claim 16 A step of preparing an intermediate by heating and cooling a carbon precursor mixture; a step of preparing a pulverized material by grinding the intermediate; a step of performing an activation heat treatment on the pulverized material; a step of preparing a porous sintered material by calcining the activated pulverized material at 900°C or higher; a step of chemically vaporizing (CVI) silicon precursor gas into the pores of the sintered material; and a step of preparing a composite having a first coating layer formed on the outer surface of the sintered material by heat-treating the sintered material using a hard coating material. A method for manufacturing a negative electrode material for a lithium secondary battery, comprising the step of heat-treating a first mixture including the composite and graphene to form a second coating layer on the outer surface of the composite; wherein the negative electrode material for a lithium secondary battery comprises a porous carbon carrier, nanosilicon filled in the pores of the carbon carrier, a first coating layer formed on the outer surface of the carbon carrier, and a second coating layer formed on the outer surface of the first coating layer and having a lower hardness than the first coating layer, wherein the carbon carrier has a higher hardness than the second coating layer, and the negative electrode material has a D-band peak intensity (I) relative to the G-band peak intensity in a Raman spectrum D / I G A method for manufacturing a negative electrode material for a lithium secondary battery, wherein ) is 1.3 or less. Claim 17 A method for manufacturing a cathode material according to claim 16, wherein the first mixture is heat-treated at 600 to 1100°C to form the second coating layer. Claim 18 A method for manufacturing a negative electrode material for a lithium secondary battery according to claim 16, wherein the carbon precursor mixture comprises a carbon precursor and a crosslinking agent, and the carbon precursor comprises one or more of an organic polymer and an inorganic polymer, wherein the organic polymer comprises one or more of cellulose, celluloid, nylon, polyacrylic, phenolic resin, melamine, polyvinyl chloride, polystyrene, polyethylene, hydrogenated nitrile butadiene rubber (H-NBR), nitrile butadiene rubber (NBR), polyvinylidene fluoride (PVDF), and styrene butadiene rubber (SBR), the inorganic polymer comprises one or more of polysiloxane, polyphosphazene, and polyphosphate, and the crosslinking agent comprises one or more of urea and amine-based compounds. Claim 19 A method for manufacturing a negative electrode material for a lithium secondary battery according to claim 16, wherein the intermediate is manufactured by including the step of heating the carbon precursor mixture to 80 to 250°C and then cooling it to 0°C or lower. Claim 20 A method for manufacturing a negative electrode material for a lithium secondary battery, wherein, in claim 16, the activation heat treatment is performed at 650 to 1150°C. Claim 21 A method for manufacturing a negative electrode material for a lithium secondary battery according to claim 16, wherein the calcination comprises: a step of first calcining the activated pulverized material by heating and maintaining it at a pressure of 2 to 8 atm to 900 to 1100℃; and a step of secondarily calcining the first calcined pulverized material at a pressure of 0.5 to 0.8 atm to 1100 to 1700℃. Claim 22 In paragraph 16, the silicon precursor gas is silane (SiH4), disilane (Si2H6), trisilane (Si3H8), tetrasilane (Si4H 10 A method for manufacturing a negative electrode material for a lithium secondary battery comprising one or more of ), chlorosilane and methylchlorosilane. Claim 23 In claim 16, the above chemical vapor deposition is carried out at 300 to 900°C. A method for manufacturing a negative electrode material for a lithium secondary battery. Claim 24 A method for manufacturing a negative electrode material for a lithium secondary battery, wherein, in claim 16, the first coating layer is formed by including the step of heat-treating the sintered product at 500 to 1200°C using a hard coating material. Claim 25 A lithium secondary battery comprising: a positive electrode; a negative electrode; and an electrolyte formed between the positive electrode and the negative electrode; wherein the negative electrode comprises a negative electrode material according to any one of claims 1 to 7 and claims 9 to 15.

Citation Information

Patent Citations

  • A silicon-carbon composite material and its preparation method

    CN113659125B

  • Negative active material for rechargeable lithium battery, method of preparing the same, and negative electrode and rechargeable lithium battery including the same

    KR101461220B1

  • Layered high-capacity electrodes

    KR1020200106174A

  • Electrode for lithium secondary battery having encapsulated active materials and method of manufacturing the same

    KR1020220133152A

  • Multi-shell Anode Active Material, Manufacturing Method thereof and Lithium Secondary Battery Comprising the Same

    KR102194750B1